Xerostomia: Analysis among dental patients - Karama MT Al-Nuaimy; Tahani A Al-Sandook (University of Mosul, College of Dentistry, 2005)
Abstract The present study was conducted to estimate the incidence of xerostomia (dry mouth) among 200 dental patients had different systemic diseases, including hypertension, diabetes, cardiovascular (CV) problems, anemia, arthritis and cancer. Distribution of xerostomia according to the type of systemic disease, age and sex was analyzed. In this study, 64% of total patient represent xerostomia, 24.5% of xerostomic cases were males, while 39.5% were females. Incidence of xerostomia was correlated directly with age where 16% of xerostomic patients were limited in age group between 21-40 years, while 48% of xerostomic patients were limited in the age group between 41-60 years. The results concluded that systemic disease played role in development of xerostomia which could be due to underlying medical condition, or due to their medication intake. Patients complained from xerostomia were instructed for good oral hygiene and increase their water intake. In certain cases, pilocarpine was indicated to relieve their symptoms.